THERMODYNAMICS OF AQUEOUS URANYL ION: APPARENT AND PARTIAL MOLAR HEAT CAPACITIES AND VOLUMES OF AQUEOUS URANYL PERCHLORATE FROM 10 TO 55°C - Hovey J.K.; Nguyen-trung C.; Peter R T. (My University, 1989)
Apparent molar heat capacities and volumes of aqueous solutions containing UO2(ClO4)2 in dilute (≈0.06 molal) HClO4 have been determined from 10 to 55°C. These results have been analyzed using Young's rule to obtain apparent molar volumes and heat capacities for the solute UO2(ClO42). The temperature dependences of the conventional standard-state heat capacity and volume functions for UO22+ (aq) are well represented by the following equations: that are valid from 10 to 55°C. These results differ substantially from results of earlier measurements employing different uranyl salts. These differences are likely due to the presence of ion-paired or hydrolyzed U (VI) species in the earlier studies.